Hume's Objection from Evil to the Design Argument and Skeptical Theism - Amir Saemi; Seyed Mohammad Hadi Hedayatzadeh Razavi (پژوهشنامه فلسفه دین, 2020)
Abstract. In Dialogues Concerning Natural Religion, Hume seeks to refute the teleological argument on the basis of the existence of evil in the world. This paper addresses this main objection of Hume’s. I will discuss whether a skeptical theist, in particular, is in a position to answer Hume’s objection. The problem for skeptical theists is that Hume’s objection to the design argument is structurally symmetrical to their solution to the problem of evil. I will argue that this structural symmetry can be specified in two ways, which I will call “unknown reasons for the design” and “ignorance of God’s reasons”. I will argue that while the first symmetry is not threatening to the design argument, the second symmetry poses a serious problem for the design argument. Nevertheless, I will argue that a theist may be able to respond to the problem, provided that she weakens her conclusion sufficiently, and that she takes onboard certain assumptions.